COMPARATIVE STUDY OF ONLINE SHOPPING VOCABULARY IN ENGLISH AND UZBEKI (TAMADDUN NURI JURNALI, 2024)
In this article, we will consider the comparative study of the lexicon based on the market economy and related to trade in English and Uzbek languages. We provide solutions to the comparative problems of the lexicon in the translation of business terms from one language to another. In addition, we will cite the scientific works and literature of several translators in connection with this article.